Tài liệu tham khảo "Công nghệ phần mềm" - Sommerville, Ian (Addison-Wesley, 2023)
The aim of the book is to provide a general introduction to software engineering. It introduces important concepts such as software processes and agile methods, and describe essential software development activities, from initial software specification through to system evolution.